THE INTEGRATION OF “HOME, MONASTERY AND SCHOOL” LEARNING ORGANIZATION IN THE STUDY OF LOCAL TOURIST ATTRACTIONS AND CULTURE - Kosarassawadee, Nithiwadee; Sukweses, Aungkana; Tantarangsee, Chaiwat (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The purpose of this study are to study the community’s and the monk’s satisfaction of the knowledge exchanging activity among ‘Home, Monastery and School’ learning organization, and to study the students’ satisfaction of the integration of such learning organization in the study of local tourist attractions and culture. Samples selected purposively include 51 subjects, namely 38 local people, 1 monk and 12 English Major Students attending the knowledge exchanging activity, at the Monastery. The data of this descriptive survey is collected from a questionnaire, and the statistics employed include percentage, mean, and S.D. The study discloses the findings as follows: 1) the overall level of the community’s and the monk’s satisfaction of the knowledge exchanging activity among ‘Home, Monastery, and School’ learning organization is in high level, while the overall students’ satisfaction in the integration of such learning organization in the study of local tourist attractions and culture is in highest level. 2) In terms of item analysis, the aspect of the community’s and monk’s satisfaction in highest level of mean scores includes passing on knowledge to next generation, while the aspect of the students’ satisfaction in highest level include exchanging knowledge in learning organization. It can be concluded that the integration of learning organization in classroom instructions enriches community’s life-long learning and students’ engagement as well as motivation.